The Opportunity Costs of Mandatory Military Service: Evidence from a Draft Lottery - Bingley, Paul; Lundborg, Petter; Lyk-Jensen, Stéphanie Vincent (Journal of Labor Economics, 2020)
Conscription forces young men to serve in the military, irrespective of their opportunity costs. Using random assignment in the Danish draft lottery, we find a negative average effect of peacetime military service on earnings, an effect varying by ability, with high-ability men facing a $23,000 lifetime earnings penalty but with low-ability men facing none. This gradient is robust to different measures of labor market prospects. Educational disruption is an important mechanism, while service has little effect on health or criminal activity. The opportunity costs of conscription are borne by men with the best labor market prospects.